Peningkatan Kualitas Pembelajaran Peserta Didik melalui Implementasi Supervisi Akademik - Senang Senang; Sunardi Sunardi; Muhamad Wildan Farchani (Academicus: Journal of Teaching and Learning, 2024)
Academic supervision plays a crucial role in improving the quality of learning. In the context of education, academic supervision aims to provide guidance and support to teachers in performing their duties, thereby enhancing the quality of the learning process and student outcomes. This study aims to explore how academic supervision can contribute to the improvement of learning, identify effective strategies in the implementation of academic supervision, and understand the challenges faced in the process. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis. The research participants consist of school principals, academic supervisors, and teachers from SMP Terpadu Mambaul Huda Ngoro Jombang. The research findings indicate that academic supervision has a positive impact on improving the quality of learning. Effective supervision strategies include classroom observation, constructive feedback, and continuous training for teachers. However, the study also identifies several challenges such as lack of resources, high workload, and resistance from some teachers towards the supervision process. Overall, the study concludes that structured and continuous academic supervision can help improve teacher competence and student learning outcomes. The implementation of appropriate supervision strategies and support from all stakeholders are essential to overcome existing challenges and achieve the goal of improving learning quality.